Climate justice and litigation in the context of South Africa - Chihombe, Denmark (North-West University, 2025)
This study interrogates the intersection of climate justice and litigation in the South African context. It addresses the urgent need for legal methods to address the disproportionate impact of climate change on marginalised communities. As climate change has become one of the greatest global challenges, marginalised communities most keenly feel its impacts, particularly those historically disadvantaged by socioeconomic inequalities rooted in apartheid. What follows is a critical examination of the most important international climate frameworks, in particular the United Nations Framework Convention on Climate Change (hereinafter UNFCCC) and the Paris Agreement, which have shaped the global discourse on climate change. The increasing recognition of the rights of historically marginalised and vulnerable communities underscores the potential role of climate litigation in achieving climate justice for all by holding both government and corporations accountable for their actions and lack thereof in mitigating climate change. The study examines the South African legal framework and recognises its progressive constitution that guarantees environmental rights. On the other hand, the study highlights significant barriers to effective climate action, particularly for the country’s most vulnerable, poor and marginalised populations, who often lack access to legal resources and skills needed for climate action. Using decided climate cases such as Earthlife Africa v. Minister of Environment, the study highlights the problems that plaintiffs often face when it comes to proving causation and the need for expert evidence in such litigation. Finally, the study concludes that while climate litigation offer opportunities for climate justice, the challenges identified need to be addressed to ensure the effectiveness of climate processes in achieving climate justice. The study therefore makes recommendations for strengthening legal aid, promoting public climate litigation and improving community capacity. By implementing these recommendations, climate justice will be achieved so that South Africa can effectively utilise climate litigation to demand climate justice for both current and future generations.
Keywords: Climate change; Global challenges; Justice; Litigation; Marginalised communities

The Influence of Corporate Sustainability Laws on Multi-Stakeholder Initiatives to Eliminate Forced and Child Labour in Supply Chains - Fanou, Temisan (McMaster University, 2024)
An array of governance initiatives has emerged to address forced labour and labour exploitation in global value chains (GVCs). Drawing on the transnational business governance interactions theoretical framework, as well as Timothy Bartley’s place-conscious transnational governance model, this thesis examines the interaction between two of these hybrid forms of governance: multi-stakeholder initiatives and corporate sustainability laws. I conduct a case study of the cocoa sector, and specifically of the multinational company, Nestlé, using multiple qualitative research methods including legal analysis, key informant interviews, and documentary analysis. My research suggests that the layering of corporate sustainability laws, and particularly the French Duty of Vigilance Law, on top of CSR and MSIs in the cocoa sector, is not addressing the governance gap that permits corporations to evade accountability for human rights abuses in their supply chain. I find that the introduction of corporate sustainability laws may have contributed to a decrease in Nestlé's efforts to address labor violations in certain areas, while in others, it appears to have supported the continuation of existing practices. This raises implications for the continuous efforts in various jurisdictions to introduce these laws as a solution to the shortcomings of private, voluntary rule-making systems. Further research is required to explore how these governance mechanisms are interacting in other sectors, in companies of different sizes, and within various types of MSIs. This will help identify the factors that influence interactions and shed further light on the path forward for policymakers.

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty